Beverages formulated with whey protein and added lutein - Rocha, Juliana de Cássia Gomes; Mendonça, Adriana Corrêa; Viana, Kéllen Wanessa Coutinho; Maia, Mariza de Paiva; Carvalho, Antônio Fernandes de; Minim, Valéria Paula Rodrigues; Stringheta, Paulo César (Ciência Rural, 2017)
This study aimed to develop and characterize beverages formulated with whey protein and added lutein. Beverages formulated with 0.5 (F1), 2.0 (F2), 4.0 (F3) and 6.0% w/v (F4) whey protein were physicochemically and microbiologically characterized, and sensory evaluated. The physicochemical analyses indicated that the protein content significantly changed (P<0.05) the acidity values, soluble solids and the colorimetric coordinates, making possible to adjust mathematical models for all these variables. Microbiological analyses showed no significant contamination (P<0.05) during processing that would compromise drinks quality of the drinks. Carotenoid content and the antioxidant activity did not change significantly (p>0.05) with increased protein content. The F2 formulation showed the highest sensory acceptance. Beverages offer a promising alternative to whey use and enhance the value of the product by the addition of lutein.

Este estudo teve como objetivo desenvolver e caracterizar bebidas formuladas com proteinas de soro de leite adicionadas de luteina. Bebidas formuladas com 0,5 (F1), 2,0 (F2), 4,0 (F3) e 6,0% m/v (F4) de proteinas de soro caracterizadas fisico-quimicamente e microbiologicamente e, avaliadas sensorialmente. As analises fisico-quimicas indicaram que o teor de proteina alterou significativamente (P<0,05) os valores de acidez, solidos soluveis e as coordenadas colorimetricas, foi possivel ajustar modelos matematicos para todas essas variaveis. As analises microbiologicas mostraram contaminacao nao significativa (P<0,05) durante o processamento que poderia comprometer a qualidade das bebidas. Os teores de carotenoides e a atividade antioxidante nao variaram significativamente (P>0,05) com o aumento do teor de proteina. A formulacao F2 apresentou a maior aceitacao sensorial. As bebidas sao uma alternativa promissora para o uso do soro de leite e aumentam o valor agregado do produto pela adicao de luteina.
Keywords: Antioxidant activity; Lutein; Proteins; Protein drink; Sensory acceptance; Whey; Atividade antioxidante; Luteina; Proteinas; Bebida proteica; Aceitação sensorial; Soro de leite